Dwelling Time Analysis Using Dynamic System Model in the Implementation of National Logistics Ecosystem at Port Jakarta International Container Terminal - Ridho Hans Gurning; Achmad Riadi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Efficient dwelling time loading and unloading at the port has been widely done. Behind this research was carried out the implementation of the National Logistics Ecosystem (NLE) by using a dynamic system to reduce dwelling loading and unloading time at the Port of Jakarta International Container Terminal. The purpose of research were to find out the development of dynamic system models and the impact of NLE implementation in reducing dwelling time. This research method used dynamic system models and validation tests with behavior pattern tests. The validation results of the dynamic system model were obtained dwelling time between 2.79 - 4.56 days, mean error by 3% and standard deviation error by 11% and the implementation of NLE caused a decrease in dwelling time between 0.96 - 2.30 days, resulting in a decrease in dwelling time by 70%. The results of simulated container flows between 120,909 - 195,212 containers, mean error by 0% and standard deviation error by 19% with the application of NLE container flows between 132,952 - 200,077 containers. The results of the simulation of unloading quantity of 67,295 – 103,342 TEU's, mean error by 1% and standard deviation error by 24% with the application of NLE between 86,169 – 108,032 TEU's, average – average of 96,712 TEU's / month, there was an increase in the quantity of unloading by 130 TEU's / month. The implementation of NLE can be applied to port operationsKeywords: Dwelling Time, Port, National Logistic Ecosystem, Dynamic System Model